Meta-Analysis: Correlations between Knowledge, Self-Efficacy, and Social Support on HIV testing in Homosexual - Karismatika Surya Gumilar; Argyo Demartoto; Bhisma Murti (Journal of Health Promotion and Behavior, 2024)
Background: HIV is an infectious disease for which there is no cure. Homosexuals are a vulnerable group for HIV transmission. One of the HIV-AIDS control programs is to make HIV testing a standard of service in all health facilities. This study aims to analyze the influence of self-efficacy, social support, and knowledge in carrying out HIV tests on homosexuals. Subjects and Method: This study is a systematic and meta-analysis study, with PICO as follows: Population= Homosexual. Intervention= Good knowledge, high self-efficacy, and high social support. Comparison= Poor knowledge, low self-efficacy, and low social support. Outcome= Use of HIV Testing. The articles used in this research were obtained from several databases including PubMed, Google Scholar and Scopus. These articles were collected over 2 weeks. The keywords to search for articles are as follows: "HIV Test AND Homosexual AND Knowledge AND Self Efficacy AND Social Support". The articles included in this research were full-text articles with a cross-sectional study design. Articles were collected using PRISMA flow diagrams. Articles were analyzed using Review Manager 5.3 application. Results: A total of 12 articles were reviewed in this meta-analysis research originating from China, Guatemala, Myanmar, USA, Jamaica. The study showed that homosexuals with good knowledge (aOR= 2.02; 95% CI= 1.38 to 2.96; p= 0.003), social support high (aOR= 1.17; 95% CI= 1.03 to 1.34; p= 0.020), and high self-efficacy (aOR= 1.11; 95% CI= 1.02 to 1.22; p= 0.010) has a significant influence on the decision to test for HIV. Conclusion: Good knowledge, high self-efficacy, and high social support can increase the willingness to carry out HIV testing among homosexuals.